2020
DOI: 10.32479/irmm.10680
|View full text |Cite
|
Sign up to set email alerts
|

Lean Six Sigma Effect on the Quality of the Products in Jordanian Food Companies: The Moderating Role of the Manufacturing Process

Abstract: The purpose of this study is to determine the effect of lean six sigma and the quality of the product and manufacturing process. Further, its focus on understanding the impact on the defect, over production, Motion, Waiting time, through the role of Manufacturing Process on quality of products. The study applied the questionnaire, which was adapted from past literature. The questionnaire was distributed to a sample of 180 respondents, and the number of returned items was 142. The study applied a purposive samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…It is confirmed that the six sigma initiative will bring better results, increase sigma value hence will reduce defects (Murumkar et al 2018;Husen et al 2021). This result also confirm with the previous study on six sigma initiatives that six sigma affected quality (Omoush 2020).…”
Section: Resultssupporting
confidence: 82%
“…It is confirmed that the six sigma initiative will bring better results, increase sigma value hence will reduce defects (Murumkar et al 2018;Husen et al 2021). This result also confirm with the previous study on six sigma initiatives that six sigma affected quality (Omoush 2020).…”
Section: Resultssupporting
confidence: 82%
“…During the analysis phase, widely known tools such as cause and effect diagrams (CED), why-why analysis, tree diagrams are used to identify the root causes (Sarkar et al, 2017). Whether the source of the problem is an inefficient process or a defect issue, the true impact of incorporating Six Sigma elements into the manufacturing process to achieve the highest quality products that satisfy customers is required (Omoush, 2020).…”
mentioning
confidence: 99%